Educational Simulation Videos for Performing Resuscitative Endovascular Balloon Occlusion of the Aorta - Sung Wook Chang; Dong Hun Kim; Ye Rim Chang (Journal of Trauma and Injury)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been accepted as an adjunct procedure for non-compressible torso hemorrhage in patients with hemorrhagic shock. With appropriate indications, REBOA should be performed for resuscitation regardless of the physician’s specialty. Despite its effectiveness in traumatized patients with hemorrhagic shock, performing REBOA has been challenging due to physicians’ lack of experience. Even though training in endovascular skills is mandatory, many physicians cannot undergo sufficient training because of the limited number of endovascular simulation programs. Herein, we share simulation video clips, including those of a vascular circuit model for simulation; sheath preparation; long guidewire and balloon catheter preparation; ultrasound-guided arterial access; sheath insertion or upsizing; and balloon positioning, inflation, and migration. The aim of this study was to provide educational video clips to improve physicians’ endovascular skills for REBOA.